Single‐center serological surveillance of SARS‐CoV‐2 in pregnant patients presenting to labor and delivery. Issue 3 (8th December 2022) - Boggess, Kim A.; Stringer, Elizabeth M.; Robinson, Whitney R.; Munoz, M. Cristina; Goodnight, William H.; Rahangdale, Lisa; Vora, Neeta L.; Rosenbaum, Alan J.; Bala, Vidhya; Ivins, Amber; Narowski, Tara M.; Jadi, Ramesh; et al.
Abstract: Objective: To measure maternal/fetal SARS‐CoV‐2 antibody levels. Methods: A prospective observational study of eligible parturients admitted to the hospital for infant delivery was conducted between April and September 2020. SARS‐CoV‐2 antibody levels were measured in maternal and umbilical cord specimens using an in‐house ELISA based on the receptor‐binding domain (RBD) of the spike protein. Among SARS‐CoV‐2 seropositive patients, spike RBD antibody isotypes (IgG, IgM, and IgA) and ACE2 inhibiting antibodies were measured. Results: In total, 402 mothers were enrolled and spike RBD antibodies in 388 pregnancies were measured (336 maternal and 52 cord specimens). Of them, 19 were positive (15 maternal, 4 cord) resulting in a seroprevalence estimate of 4.8% (95% confidence interval 2.9–7.4). Of the 15 positive maternal specimens, all had cord blood tested. Of the 15 paired specimens, 14 (93.3%) were concordant. Four of the 15 pairs were from symptomatic mothers, and all four showed high spike‐ACE2 blocking antibody levels, compared to only 3 of 11 (27.3%) from asymptomatic mothers. Conclusion: A variable antibody response to SARS‐CoV‐2 in pregnancy among asymptomatic infections compared to symptomatic infections was found, the significance of which is unknown. Although transfer of transplacental neutralizing antibodies occurred, additional research is needed to determine how long maternal antibodies can protect the infant against SARS‐CoV‐2 infection. Synopsis: Among pregnant women infected with COVID‐19, transfer of transplacental neutralizing antibodies was efficient in participants with high levels of RBD IgG.